Interruption or deferral of antiretroviral therapy reduces markers of bone turnover compared with continuous therapy: The SMART body composition substudy. (21st May 2013) - Hoy, Jennifer; Grund, Birgit; Roediger, Mollie; Ensrud, Kristine E; Brar, Indira; Colebunders, Robert; Castro, Nathalie De; Johnson, Margaret; Sharma, Anjali; Carr, Andrew; ,
ABSTRACT Bone mineral density (BMD) declines significantly in HIV patients on antiretroviral therapy (ART). We compared the effects of intermittent versus continuous ART on markers of bone turnover in the Body Composition substudy of the Strategies for Management of AntiRetroviral Therapy (SMART) trial and determined whether early changes in markers predicted subsequent change in BMD. For 202 participants (median age 44 years, 17% female, 74% on ART) randomized to continuous or intermittent ART, plasma markers of inflammation and bone turnover were evaluated at baseline and months 4 and 12; BMD at the spine (dual‐energy X‐ray absorptiometry [DXA] and computed tomography) and hip (DXA) was evaluated annually. Compared with the continuous ART group, mean bone‐specific alkaline phosphatase (bALP), osteocalcin, procollagen type 1 N‐terminal propeptide (P1NP), N‐terminal cross‐linking telopeptide of type 1 collagen (NTX), and C‐terminal cross‐linking telopeptide of type 1 collagen (βCTX) decreased significantly in the intermittent ART group, whereas RANKL and the RANKL:osteoprotegerin (OPG) ratio increased (all p ≤ 0.002 at month 4 and month 12). Increases in bALP, osteocalcin, P1NP, NTX, and βCTX at month 4 predicted decrease in hip BMD at month 12, whereas increases in RANKL and the RANKL:OPG ratio at month 4 predicted increase in hip and spine BMD at month 12. This study has shown that compared with continuous ART, interruption of ART results in a reduction in markers of bone turnover and increase in BMD at hip and spine, and that early changes in markers of bone turnover predict BMD changes at 12 months.